2016
DOI: 10.1080/17843286.2016.1174393
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of gastric bypass surgery on psychosocial well-being and eating behavior: not all that glitters is gold

Abstract: Seven years post-RYGB, patients reported a significant improvement of physical health and higher satisfaction with daily life, but not with social relationships or sexual performance. Eating behavior post-RYGB was more influenced by external cues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Qualitative analysis indicated an improvement in emotional eating in the first 12 months after bariatric surgery 25–28,31,34,37,39–43 , and mixed findings thereafter. The observation in longitudinal studies that early postoperative changes in emotional eating may not be sustained in the longer term are consistent with findings from cross‐sectional studies comparing patients at 24–68 months after LAGB with presurgical controls 48 and patients at 7 years post‐RYGB with control groups with obesity 49 , as well as with a 2016 systematic review by Opozda and colleagues 50 which examined preoperative and postoperative emotional eating patterns, mostly after RYGB.…”
Section: Discussionsupporting
confidence: 80%
“…Qualitative analysis indicated an improvement in emotional eating in the first 12 months after bariatric surgery 25–28,31,34,37,39–43 , and mixed findings thereafter. The observation in longitudinal studies that early postoperative changes in emotional eating may not be sustained in the longer term are consistent with findings from cross‐sectional studies comparing patients at 24–68 months after LAGB with presurgical controls 48 and patients at 7 years post‐RYGB with control groups with obesity 49 , as well as with a 2016 systematic review by Opozda and colleagues 50 which examined preoperative and postoperative emotional eating patterns, mostly after RYGB.…”
Section: Discussionsupporting
confidence: 80%
“…Thirdly, the 1-year follow-up might have been too short. Several studies reported long-term recidivism in eating pathologies, notably in those patients who experience weight regain [32,43]. Fourthly, the majority of patients in our cohort were female and underwent RYGB, therefore the overall outcomes (EDE-Q scores, comorbidity resolution, surgical complications) are less generalizable to males and to patients who undergo SG.…”
Section: Discussionmentioning
confidence: 86%
“…For instance, there are some reports of some reduced anxiety after bariatric surgery [ 47 , 48 ]. Whereas RYGB and VSG in humans weight loss appears to improve quality of life [ 49 , 50 ] and reduce levels of depression [ 51 , 52 ], when anxiety is probed specifically, there are some short-term improvements [ 47 , 53 , 54 ] or no significant change [ 48 , 52 , 53 , 55 ] or even a decline of the anxiolytic improvements of surgery over time [ 54 ]. Therefore the timing of the tests and tissue measurements with we performed in these studies with respect to the timing of the surgery could further complicate our current interpretations.…”
Section: Discussionmentioning
confidence: 99%